2019
DOI: 10.1002/rcs.2066
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between single‐site and multiport robot‐assisted hysterectomy in obese patients with endometrial cancer: An Italian multi‐institutional study

Abstract: Background The aim of this study is to compare robotic single‐site hysterectomy (RSSH) and robotic multiport hysterectomy (RMPH) for endometrial cancer (EC) in obese patients in terms of surgical outcomes. Methods This retrospective study compares RSSH with RMPH in obese patients with EC and FIGO stages I to II divided in three classes according to their body mass index (BMI): class A (30‐34.9 kg/m2), class B (35‐39.9 kg/m2), and class C (>40 kg/m2). Results We included 225 patients (RSSH: 76; RMPH: 149). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…These factors may have limited the adoption of MAS for common gynecological procedures such as hysterectomy and sacrocolpopexy 9,10 . Robot‐assisted surgery offers improved dexterity, precision, and three‐dimensional visualization 11,12 and can extend MAS feasibility for patients with complex pathologies or higher body mass indices (BMIs) 13 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors may have limited the adoption of MAS for common gynecological procedures such as hysterectomy and sacrocolpopexy 9,10 . Robot‐assisted surgery offers improved dexterity, precision, and three‐dimensional visualization 11,12 and can extend MAS feasibility for patients with complex pathologies or higher body mass indices (BMIs) 13 …”
Section: Introductionmentioning
confidence: 99%
“…9,10 Robot-assisted surgery offers improved dexterity, precision, and three-dimensional visualization 11,12 and can extend MAS feasibility for patients with complex pathologies or higher body mass indices (BMIs). 13 Versius (CMR Surgical, Cambridge, UK), a next-generation robotic surgical system, aims to improve patient outcomes and enduser experience. [14][15][16][17] The device comprises practical-sized mobile bedside units to provide maximum flexibility in the operating room (OR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By shortening the learning curve, these advantages may enable more surgeons to perform complex MAS procedures, and could extend the feasibility of MAS to a greater body of surgeons [2]. In addition, robot-assisted MAS could be feasible in a wider range of patients, such as those with a higher body mass index (BMI) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Conversion rate, the intraoperative transition from a robotic procedure to an alternative surgical approach, was reported by three studies [28,29,31]. Two studies reported that no patients required a conversion in both single-port and multiport approaches [28,31].…”
Section: Conversion Ratementioning
confidence: 99%